ENVIRONMENTAL IMPACT OF FISH FARMING IN FLOATING CAGES IN ISLA ARENA, CAMPECHE - Yadira Silva-Cruz; MarÃa del Refugio CastaÃ±eda-ChÃ¡vez; Fabiola Lango-Reynoso; CesÃ¡reo Landeros-SÃ¡nchez (Tropical and Subtropical Agroecosystems, 2011)
Mariculture is the cultivation of marine species of commercial importance. This activity has intensified in recent decades due to the need for food production. The present study evaluated the impact of Rachycentron canadum (Cobia) and Sciaenops ocellatus (Red Drum) farming in floating cages along the coasts of Campeche, Mexico. The impact of this mariculture system was evaluated through the physicochemical analysis of the sediment from underneath the cages and the analysis of the quality of the water from the farming area. Results showed high concentrations of nitrogen (> 0.5 %) and organic matter (> 80 %), both in the farming area and in the control sites. The concentration of fine sediment showed no spatial or temporal changes. There were no detectable concentrations of nitrites, nitrates, ammonium and phosphates in the water, in a range of 0.1 to 100 mg L-1. The impact caused by this farming system appeared to be non significant, at least in the area of study, due to the constant movement of the water caused by ocean currents which, very likely, carried the waste from the cages to other places.